Standardisation and quality control of ultrasound measurements taken in the INTERGROWTH‐21st Project. (11th July 2013) - Sarris, I; Ioannou, C; Ohuma, EO; Altman, DG; Hoch, L; Cosgrove, C; Fathima, S; Salomon, LJ; Papageorghiou, AT; ,
Abstract : Meticulous standardisation and ongoing monitoring of adherence to measurement protocols during data collection are essential to ensure consistency and to minimise systematic error in multicentre studies. Strict ultrasound fetal biometric measurement protocols are used in the INTERGROWTH‐21 st Project so that data of the highest quality from different centres can be compared and potentially pooled. A central Ultrasound Quality Unit (USQU) has been set up to oversee this process. After initial training and standardisation, the USQU monitors the performance of all ultrasonographers involved in the project by continuously assessing the quality of the images and the consistency of the measurements produced. Ultrasonographers are identified when they exceed preset maximum allowable differences. Corrective action is then taken in the form of retraining or simply advice regarding changes in practice. This paper describes the procedures used, which can form a model for research settings involving ultrasound measurements.